Reevaluasi Penyelesaian Sengketa Perbankan Melalui Badan Penyelesaian Sengketa Konsumen - Radhyca Nanda Pratama; Akbar Fitri Yanto Solehudin; Dilla Nurfiana Astanti (Universitas Bengkulu, 2021)
The establishment of LAPS in the banking financial services sector in accordance with the mandate of the UU OJK as an institution that has authority in the settlement of consumer disputes outside the court (non-litigation) through the units of financial service institutions contained in the list of alternative Dispute Resolution Institutions established by the OJK. Before the establishment of LAPS, dispute resolution outside the court was conducted through BPSK which had the authority as stipulated in the UUPK. However, the existence of the same authority as the institution for resolving disputes outside the court between BPSK and LAPS raises legal uncertainty. The purpose of this study is to analyze the dispute resolution of financial services institutions in the banking sector after and before LAPS was formed and enacted. The method used in this study is a normative legal research method using a research approach, statue approach and a conceptual approach. The results of this study are the choice of financial services sector consumer dispute resolution forums constituting consumer rights based on consumer protection laws. The existence of LAPS is the implementing regulation of the UU OJK so that consumers can choose to settle disputes through the LAPS financial services sector without prejudice to the settlement of consumer disputes outside the court stipulated in the UUPK. Keywords: Dispute; Bangking; LAPS. Pembentukan LAPS sektor jasa keuangan perbankan sesuai dengan amanat UU OJK sebagai lembaga yang memiliki kewenangan dalam penyelesaian sengketa konsumen di luar pengadilan (non-litigasi) melalui unit-unit lembaga jasa keuangan yang termuat dalam daftar Lembaga Alternatif Penyelesaian sengketa yang ditetapkan oleh OJK. Sebelum hadirnya LAPS, penyelesaian sengketa di luar pengadilan dilakukan melalui BPSK yang memiliki kewenangan sebagaimana ditetapkan dalam UUPK. Namun, adanya kewenangan yang sama sebagai lembaga penyelesaian sengketa di luar pengadilan antara BPSK dengan LAPS menimbulkan ketidakpastian hukum. Tujuan dari penelitian ini adalah untuk menganalisis penyelesaian sengketa lembaga jasa keuangan sektor perbankan sesudah dan sebelum dibentuk dan ditetapkannya LAPS. Metode yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif dengan menggunakan pendekatan penelitian, pendeketan perundang-undangan (statute approach) dan pendekatan konsep (conceptual approach). Hasil dari penelitian ini adalah pilihan forum penyelesaian sengketa konsumen sektor jasa keuangan merupakan hak konsumen berdasarkan hukum perlindungan konsumen. Keberadaan LAPS merupakan peraturan pelaksana dari UU OJK sehingga konsumen dapat memilih untuk menyelesaikan sengketa melalui LAPS sektor jasa keuangan dengan tidak mengesampingkan penyelesaian sengketa konsumen di luar pengadilan yang diatur dalam UUPKKata kunci: Sengketa; Perbankan; LAPS.